EU Membership and Long-term Economic Growth - Cuckova, Sara; Slaný, Martin, 1982-; Máslo, Lukáš Augustin, 1985-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2024)
This thesis examines the impact of European Union membership on long-term economic growth across three countries (Czechia, Poland and Slovakia). Examinations into the subject area through a Solow model structure and its components of capital, labour and total factor productivity. According to statistical tests the appropriate analytical methods are selected for each country. From the analysis, it is evident that capital and total factor productivity drive gross domestic product growth across all the countries. However, the same can’t be said for labour, it is apparent that it has a negative impact on Poland’s economy. More importantly it is evident that European Union membership demonstrates a predominantly positive influence on economic growth. In the majority of the countries, Poland and Slovakia, it displays a positive impact, but not the same can be said for Czechia. These findings affirm the key aspects of the Solow model and reveal the varying impact of European Union membership on long-term economic growth across member states. Stressing the importance of considering country-specific factors. This work enriches the understanding of the impact of European Union membership and provides valuable insights for policymakers navigating European Union integration.
Vedoucí práce: Martin Slaný
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: economics [obor bakal. práce]; bakalářské práce; bachelor's theses